Study of three dimensional composites printing material through simulation - Owi, Chun Kit (2022)
Fused Deposition Modeling (FDM) 3D printing is getting popular nowadays. It can exhibit a high degree of geometric complexity by printing with molten thermoplastic by extruding it onto a heated printing bed through a nozzle. Combining materials with different mechanical properties will be one solution to achieve a 3D printed object with functionality and desired mechanical properties. Besides, it is essential to understand how printing parameters influence the mechanical properties of a 3D printed object. This study investigates the mechanical performance of 3D composite materials with different shell and infill materials through finite element analysis. In this study, different infill patterns (triangular and hexagonal), infill density (20%, 60%, and 100%), and shell thickness (0.4 mm, 0.8 mm, and 1.2 mm) were assessed. The geometry with the stated infill pattern, infill density, and shell thickness was created using SpaceClaim software for finite element analysis. A multitools 3D printer was used to fabricate the samples and validate the experimental results obtained against finite element analysis. The tensile and flexural tests were performed according to ASTM D638 and ASTM D790. Analysis of variance was used to determine the significance level of each printing parameter. The results show that the composite PLA/PETG improved tensile strength. However, there was a decrement in flexural strength compared to PLA. Composite PLA/ABS help increase tensile and flexural strength compared to ABS. Composites PLA/PA6 had higher flexural strength compared to PA6. However, its tensile strength is lower than PLA and PA6. Composite PLA/TPU and ABS/TPU improve tensile and flexural properties compared to TPU. Composite PA6/ABS has improved tensile modulus and flexural properties, but it has lower tensile strength than PA6 and ABS. The experimental verification and validation show that the average margin of error from finite element analysis and the experimental test was lower than 10%. Through ANOVA analysis, it depicts that infill density has the lowest p-value. This indicates that infill density contributes significantly to the changes in mechanical properties. The dataset obtained from the finite element analysis can be used as a reference when fabricating 3D objects.